2014
DOI: 10.1007/s11060-014-1546-7
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma specific graded prognostic assessment can predict outcomes for patients with brain metastases from hepatocellular carcinoma

Abstract: Stratifying patients with brain metastasis (BM) from hepatocellular carcinoma (HCC) by prognostic factors can be useful when making treatment decisions. Nevertheless, a diagnosis-specific graded prognostic assessment (GPA) for HCC has not been well established. We retrospectively reviewed the data from 118 HCC patients newly diagnosed with BM at the Yonsei University Health System between 1985 and 2011. After univariate and multivariate analyses of prognostic factors, those shown to significantly affect surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…4,5,[7][8][9] Consistent with previous reports, our case series showed a median survival period of 3 d in the non-treated group although it depends on the timing of the diagnosis. In our cases, Case 1, 2, 5, and 8 showed rapid progression of brain metastases after the diagnosis of extrahepatic metastatic lesions (median of 13.5 months) in lung or lymphnodes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…4,5,[7][8][9] Consistent with previous reports, our case series showed a median survival period of 3 d in the non-treated group although it depends on the timing of the diagnosis. In our cases, Case 1, 2, 5, and 8 showed rapid progression of brain metastases after the diagnosis of extrahepatic metastatic lesions (median of 13.5 months) in lung or lymphnodes.…”
Section: Discussionsupporting
confidence: 91%
“…[4][5][6][7] The prognosis of these patients is poor with survival period of a few weeks. 4,5,[7][8][9] Therefore, brain metastasis is considered as the terminal state of patients with HCC. In addition, various neurologic symptoms including headache, vomiting, hemiparesis, diplopia, hemianopsia, dysarthria, gait disturbance, and seizure affect their quality of life (QOL), and re-bleeding from the tumors cause a worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The first large retrospective study published in 1998 by Kim et al found that only seven of 3,100 HCC patients had intracranial metastases [11]. On the basis of data from 10,615 patients recorded in the Yonsei University Health System between 1973 and 2001, Lim et al suggested that the incidence had increased to 1.1% [12]. Similarly, Shao et al assessed 158 patients with advanced HCC who were treated with antiangiogenic targeted therapy at National Taiwan University Hospital between 2005 and 2009, and reported an increase in incidence to 7% [18].…”
Section: Incidence Of Brain Metastases In Hcc Patientsmentioning
confidence: 99%
“…BMHCC patients generally have advanced liver disease and a high percentage of synchronous extra-cerebral metastases (ranging from 80.5% to 93.2%), including lung (69.4-75.6%), followed by bone (18-25.8%), lymph nodes, and adrenal glands [2, 3, 12, 3036]. On the other hand, BMs from early stage HCC or without other extrahepatic metastases are occasionally reported [30].…”
Section: Characteristics Of Bmhcc Patientsmentioning
confidence: 99%
See 1 more Smart Citation